Sistem Pendukung Keputusan Pemilihan Supervisor Karyawan Dengan Menggunakan Metode ROC-SAW - Jeperson Hutahaean; Neni Mulyani; Zulfi Azhar; Aulia Khairani Nasution (JURIKOM (Jurnal Riset Komputer), 2022)
Employee leadership is someone who is influential to be a role model and example for many employees who have positions below him, a company will definitely choose to increase employees to become employee leaders as a form of appreciation to employees who have quality and good work performance for their loyalty to their work towards a company and the importance of conducting employee leadership elections to motivate and fill vacancies caused by several factors, both internal and external factors. The owner of the company strives to avoid gaps in the rights of employees so that the owner of the employee must conduct an employee leadership election by utilizing the existence of technology in making a decision. In this study, the selection of employee leadership was carried out using a decision support system with the help of the ROC-SAW method so as to get the results of the candidate or alternative A4 which became the main choice for employee leadership with a value of 85%.